Digital dividend: policies to harness the productivity potential of digital technologies - Sorbe, Stéphane; Gal, Peter N.; Nicoletti, Giuseppe; Timiliotis, Christina (Paris, 2019)
"This paper presents a range of policies to enhance adoption of digital technologies and firm productivity. It quantifies illustratively the effect of policy changes by combining the results of two recent OECD analyses on the drivers of adoption and their productivity benefits. Increasing access to high-speed internet, upgrading technical and managerial skills and implementing product and labour market reforms to facilitate the reallocation of resources in the economy are found to be the main factors supporting the efficient adoption of a selection of digital technologies. The most productive firms have benefitted relatively more from digitalisation in the past, contributing to a widening productivity gap with less productive firms. Policies should create the conditions for efficient adoption by less productive firms, which would help them to catch up, achieving a double dividend in terms of growth and inclusiveness. Enhancing skills has a key role to play in this area since less productive firms suffer relatively more from skill shortages."